2016
DOI: 10.54112/bbasr.v2016i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Association Among Morphological Traits of Lepidium Draba

Abstract: Lepidium draba is a weed plant usually grown where the conditions are moist like road side, ditch banks, rang lands and pastures. It is a fast growing weed plant that competes with crop plants for water, mineral nutrients, light and plays as a hiding place for insects. The prescribed study was carried out to evaluate morphological traits of Lepidium draba under four different locations. It was found from results that plant fresh weight and moisture contents were relatively higher for under studied locations. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…to gentamicin and 34% to ceftriaxone. These results corroborate those of Mohammedaman et al [20]. Similarly, the level of resistance of Salmonella isolates to chloramphenicol and gentamicin is lower than the results of studies carried out in Harar Qureishi et al in Addis Ababa Wasihun; and Gonder Arora et al [24] [25].…”
Section: Prevalence and Associated Risk Factors For Salmonella Spp An...supporting
confidence: 89%
See 1 more Smart Citation
“…to gentamicin and 34% to ceftriaxone. These results corroborate those of Mohammedaman et al [20]. Similarly, the level of resistance of Salmonella isolates to chloramphenicol and gentamicin is lower than the results of studies carried out in Harar Qureishi et al in Addis Ababa Wasihun; and Gonder Arora et al [24] [25].…”
Section: Prevalence and Associated Risk Factors For Salmonella Spp An...supporting
confidence: 89%
“…The prevalence of Salmonella and Shigella species isolated from all stool samples was 4.16%, which does not corroborate the result of Mohammedaman et al, [20] who found a prevalence of 9.2% were positive for Salmonella and Shigella.…”
Section: Prevalence and Associated Risk Factors For Salmonella Spp An...contrasting
confidence: 86%